2013
DOI: 10.1037/a0031389
|View full text |Cite
|
Sign up to set email alerts
|

The role of experiential avoidance in the association between borderline features and emotion regulation in adolescents.

Abstract: Difficulties in emotion regulation are one of the core features of borderline personality disorder (BPD). Individuals with BPD also report higher levels of experiential avoidance (EA) compared to controls. These constructs have never been studied concomitantly in adolescents. First, given the conceptual similarity of difficulties in emotion regulation and EA, the authors sought to determine whether EA provides incremental validity, above emotion dysregulation, in its association with borderline features. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 40 publications
1
28
0
4
Order By: Relevance
“…Although extant literature provides support for heightened exposure to violence [51, 52] and related psychological difficulties, including PTSS [51, 56] and BP pathology [54, 55], among adolescents treated in inpatient settings, no existing research has focused on examining the relationship between all of these constructs simultaneously. Thus, this study sought to extend extant literature by examining the mediating role of emotion dysregulation in the relation between exposure to violence and both PTSS and BP pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although extant literature provides support for heightened exposure to violence [51, 52] and related psychological difficulties, including PTSS [51, 56] and BP pathology [54, 55], among adolescents treated in inpatient settings, no existing research has focused on examining the relationship between all of these constructs simultaneously. Thus, this study sought to extend extant literature by examining the mediating role of emotion dysregulation in the relation between exposure to violence and both PTSS and BP pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In examining these relations, one population that may be especially important to study is adolescents in psychiatric residential treatment. Specifically, adolescents in residential treatment have been found to exhibit (a) high rates of exposure to violence [51, 52]; (b) elevated levels of emotion dysregulation [5355]; and (c) high levels of PTSS [51, 56, 57] and BP pathology [54, 55, 58]. Consistent with past research [30, 38, 44], we hypothesized that emotion dysregulation would be significantly positively associated with severity of exposure to violence, PTSS, and BP pathology in adolescents.…”
mentioning
confidence: 99%
“…Sharp et al (2011) (Schramm et al 2013). Ein vergleichbares Ergebnis wurde bei alexithymen Jugendliche gefunden (Venta et al 2012).…”
Section: Der Verlauf Psychischer Störung Von Adoleszenz Ins Erwachsenunclassified
“…B. Helmsen et al 2012;Schramm et al 2013;Zhao und Zhao 2015). Vor diesem Hintergrund erscheint die Erforschung von Emotionen und Prozessen der Emotionsregulation im Jugendalter höchst relevant.…”
Section: Introductionunclassified
“…With the exception of a few studies that include physiological measures (e.g., Evans et al, 2013), there has been little attempt in laboratory studies to examine more overt measures of emotion regulation (Aldao & Dixon-Gordon, 2014), despite the widespread concern over self report alone as a measure of impact (e.g., Rosenthal et al, 2008). Finally, these laboratory based emotional regulation manipulations have not been linked to self-reported EA despite the fact that EA mediates emotional regulation strategies in BPD (Schramm et al, 2013), and has been found to alter the impact of laboratory manipulations in nonclinical samples (e.g., Feldner Zvolensky Eifert, & Spira, 2003). Given the heterogeneity of BPD, and the known centrality of EA, it seems important to examine emotion regulation strategies with EA as a factor.…”
mentioning
confidence: 99%